Let's simplify the expression step by step:
Start with: \[ -9(-0.7h - 2h + 8) - 2h \]
First, simplify the expression inside the parentheses: \[ -0.7h - 2h + 8 = (-0.7 - 2)h + 8 = -2.7h + 8 \]
Now, substitute this back into the expression: \[ -9(-2.7h + 8) - 2h \]
Distribute \(-9\) to both terms inside the parentheses: \[ = 9(2.7h) - 9(8) - 2h \] \[ = 24.3h - 72 - 2h \]
Now, combine like terms: \[ = (24.3h - 2h) - 72 \] \[ = 22.3h - 72 \]
Therefore, the simplified expression is: \[ \boxed{22.3h - 72} \]